Employee Management Strategy at Yuki Pondok Durian Karawang Store - Mohammad Darul Fadli, Uus; Nur Ihsan, Wulan; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
The key to the success of an organization depends on its ability to manage its human resources, from recruiting workers to terminating employment. This research aims to explain how employee management is carried out, the strategies used, and the factors that become obstacles. The research approach uses qualitative. The research locus is at the Yuki Pondok Durian store on Jln. Raya Galuh Mas No.161 Karawang, West Java. The research informants were the shop owner, the head, and 2 employees. Primary data was collected through interviews, observation, documentation, and secondary data from library research. The validity test used data triangulation and content analysis. The results showed that employee management is implemented through recruitment and selection, training, performance appraisal, motivation, reward, and punishment. The strategy used is prioritizing the recruitment stage and providing motivation and rewards. The inhibiting factors in employee management are (1) some employees apply for too long vacation time, (2) some employees are dishonest by violating work rules, (3) there is a mismatch in teamwork, (4) there are employees who are not disciplined in terms of working hours.